2006
DOI: 10.1021/ic0605569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cytotoxic Effect, and Structure−Activity Relationship of Pd(II) Complexes with Coumarin Derivatives

Abstract: We report the influence of the substituent at the N atom of the ligands on the synthesis, biological activity, and stability of Pd(II) complexes of the general formula PdL(2). The compounds adopt a cis or trans configuration with respect to the substituent at the nitrogen atom. Sterically hindered substituents promote the formation of trans isomers, whereas when the nitrogen atom is unsubstituted, cis isomers are formed. The compounds were characterized by elemental analysis, infrared and 1H NMR spectroscopies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 38 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…Chromono-2(3)-carboxylic acids and their derivatives have antiarrythmic properties. Another derivative of 2-phenylchromone There have been reports of studies whereby complexes of metals with flavone derivatives were obtained or with other ligands with a similar structure (19)(20)(21)(22)(23)(24)(25)(26)(27). In these studies, the compounds displayed high biological activity which potentially lead to their application in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Chromono-2(3)-carboxylic acids and their derivatives have antiarrythmic properties. Another derivative of 2-phenylchromone There have been reports of studies whereby complexes of metals with flavone derivatives were obtained or with other ligands with a similar structure (19)(20)(21)(22)(23)(24)(25)(26)(27). In these studies, the compounds displayed high biological activity which potentially lead to their application in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68][69] This four co-ordinated Pd(II) complex 117 exists in cis-isomeric form for the ligand L (R = H) and trans-form for L (R = other than H). 67,68 Cytotoxic effects of the diones 115 and several of their Pd(II) complexes have been assessed against two leukemia cell lines HL-60 and NALM-6. On treatment with RNH 2 (R = H, Me, PhCH 2 , hexyl, cyclohexyl etc.…”
Section: Scheme 16mentioning
confidence: 99%
“…It was suggested that their biological activity depends on the nature of the ligand, the type of counterion used and the configuration of the complex. [18] For many years the research in our laboratory has been directed towards the synthesis of chromone (benzo-γ-pyrone) and coumarin (benzo-α-pyrone) derivatives and the study of their reactivity towards nucleophilic reagents containing nitrogen, oxygen, sulfur and carbon. [19] In particular, in protolytic solvents at room temperature chromones have been converted efficiently into enamine-type compounds with a typical lemon-yellow colour.…”
Section: Introductionmentioning
confidence: 99%